Clinical Evidence behind Stereotactic Radiotherapy for the Treatment of Ventricular Tachycardia (STAR)-A Comprehensive Review - Miszczyk, Marcin; Jadczyk, Tomasz; Gołba, Krzysztof; Wojakowski, Wojciech; Wita, Krystian; Bednarek, Jacek; Blamek, Sławomir (Journal of clinical medicine, 2021)
The electrophysiology-guided noninvasive cardiac radioablation, also known as STAR (stereotactic arrhythmia radioablation) is an emerging treatment method for persistent ventricular tachycardia. Since its first application in 2012 in Stanford Cancer Institute, and a year later in University Hospital Ostrava, Czech Republic, the authors from all around the world have published case reports and case series, and several prospective trials were established. In this article, we would like to discuss the available clinical evidence, analyze the potentially clinically relevant differences in methodology, and address some of the unique challenges that come with this treatment method.
Keywords: substrate ablation; ablation; radiosurgery; noninvasive; stereotactic body radiation therapy; ventricular tachycardia